(untitled) (TERRA LATINOAMERICANA, 2019)
The cocoa provides signif icant levels of carbon (C) and nitrogen (N) by the leaf litter; the change of agronomic management causes variation in the contents of these elements in the soil. The objective was to evaluate the variations of the isotopes of δ13C and δ15N between two types of cocoa (CCN51 and Nacional), located in three soil orders in the province of El Oro, Ecuador. Thirty soil samples of 0.30 m deep and 25 samples of leaf litter were taken and the abundance of the isotopes of δ13C and δ15N were analyzed. The data were analyzed including two factors, cocoa types (CCN51 and National) and order of soils (Alf isol, Entisol and Inceptisol). The results showed that the ranges of the isotope of δ13C in soil were -23.81% (CCN51, Entisol) to -26.46% (National, Entisol) and in leaf litter -27.21% (CCN51, Alf isol) to -29.86% (National, Inceptisol). The ranges of the isotope of δ15N in soil were of 7.96% (National, Entisol) and 10.48% (National, Alf isol) and in leaf litter of 4.85% (National, Entisol) to 8.38% (CCN51, Alf isol). The averages of the δ13C in the soil were plants type C3. The values of δ15N in litter and soil was an indicator of low incidence of fertilizers nitrogenous origin inorganic in National and high mineralization of N in CCN51.